Direction Changes of Isothermal Remanent Magnetization (IRM) for Multidomain Particles Produced by Stationary Alternating Field Demagnetization - Sadikun, Sahat (1990)
Single-axis and three-axis alternating field (a.f) demagnetizations of isothermal remanent magnetization (IRM) for magnetitie particles of various sizes have been investigated. Single-axis demagnetization of IRM shifted the remanent vector perpendicular to the a.faxis just before the remanence was completely removed. The angular shift when plotted against the fraction of remanence lost, did not show any dependence on particle size. Three-axis demagnetization of IRM produced progressive direction changes.